PERLIDUNGAN HUKUM BAGI KREDITUR DAN PIHAK YANG DIRUGIKAN ATAS PEMALSUAN DATA SERTIFIKAT YANG DIBEBANI HAK TANGGUNGAN: Legal Protection for Creditors and Parties harmed by Falsification of Data on Certificates encumbered by Mortgage Rights - Utama, Nadia Fitriani; Artati, Sri Untari (Faculty of Law, Universitas Trisakti, 2024)
Mortage is is a right that guarantees land to pay off certain debts, giving privileges to certain creditors compared to other creditors in accordance with the provisions in Pasal 1 ayat (1) Undang-Undang Nomor 4 Tahun 1996 on Mortgage Rights over land and objects related to Land. UUHT provides fair and balanced protection for debtors, creditors, and third parties involved. The subject matter of this research is Legal Protection for Creditors (Savings and Loan Cooperatives) and Third Parties who have ownership of land rights certificates used as collateral with the burden of unauthorized mortgage rights in Decision Number 129/G/2021/PTUN.JKT according to UUHT. This research is descriptive normative legal research is a type of study that uses secondary data and is reinforced with primary data in qualitative analysis with the deductive method to produce conclusions. Research Results (1) With the abolition of mortgage rights as a form of collateral to guarantee the payment of debts from a debtor, the creditor gets legal protection based on Pasal 18 ayat (4) UUHT. (2) Actions that are contrary to the law carried out by the debtor by pledging land rights belonging to other people without the consent of the owner as a third party, it is protected by Pasal 8 Undang-undang Nomor 4 Tahun 1996 about Mortgage Rights